THE USE OF SCRABBLE GAME TO DEVELOP VOCABULARY OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 19 PALU - Nasir, Nurul Azizah M; Rofiqoh, Rofiqoh; Patmasari, Andi (e-Journal of ELTS (English Language Teaching Society), 2025)
This research is aimed at proving whether the use of Scrabble game can develop the vocabulary of the eighth grade students of SMP Negeri 19 Palu. This research used a quasi-experimental research design with a sample of 54 students selected using a purposive sampling technique because the selected classes were VIII B and VIII C. In gathering the test, the instrument used was a vocabulary test administered twice as pre-test and post-test. The pre-test was given to the experimental and control groups before the treatment while the post-test was carried out to the experimental and control groups after the treatment. The mean score of the experimental group on pre-test was 39.77 and the control group was 46. Then, the mean score of the experimental group on post-test was 77 and the control group was 59.57. The data were statistically analyzed using the t-counted formula with degrees of freedom (df) = Nx + Ny - 2 = 26 +28 - 2 = 52. The findings show that the t-counted value is 5.896 while the t-table value is 2.006. It means that the t-counted is higher than the t-table. Therefore, the research hypothesis is accepted. It includes that Scrabble game can develop the vocabulary of the eighth grade students of SMP Negeri 19 Palu. The implication of this finding is that teachers need to use Scrabble game in teaching vocabulary designed to make students actively participate and enjoy learning English in the classroom.